Assessment of Perspective Development of Transport and Logistics Systems at Macro and Micro Level under the Conditions of Industry 4.0 Integration - Maiboroda, Olha; Майборода, Ольга; Bezuhla, Liudmyla; Безугла, Людмила Сергіївна; Gukaliuk, Andrii; Гукалюк, Андрій; Shymanska, Viktoriia; Шиманська, Вікторія; Momont, Tetiana; Момонт, Тетяна; Ilchenko, Tetiana; Ільченко, Тетяна Вікторівна (Південна Корея, IJCSNS, 2021)
The change of the development of transport and logistics systems occurs with the active change of technology and the advent of the era of Industry 4.0. It requires modernization of approaches to the development of transport and logistics systems at the macro and micro levels. The present study aims to identify perspective directions of development and evolution, find out the existing obstacles in the integration of technological solutions of transport and logistics systems at the macro and micro levels. This study is based on a quantitative and qualitative methodology for assessing the level of integration of technologies into transport and logistics systems to study the prospects for their development at the micro level. Macroeconomic indicators of transport and logistics in the context of different regions of the world were used to quantify the development prospects. For a qualitative assessment of the development of the transport and logistics system, the case study method was used. The object of the study was selected logistics company Sensco Logistics Inc., Austin TX. At the macro level, countries with more innovative logistics sectors have stronger mechanisms for coordinating private sector activities. Simplification of administrative procedures of control and regulation by the public sector in order to facilitate trade between countries is a promising direction for the development of transport and logistics systems. Such reforms are more effective in developing a “rigid” transport infrastructure. The integration of Industry 4.0 technology solutions into the international logistics sector is defined by political and legal barriers, especially in developing countries. In low-income countries, hard and soft infrastructure reforms are hindering the development of logistics companies that provide transport services. This determines the national level of development of transport and logistics systems, and in general the global level of development of transport and logistics. In developed countries, the legal barriers to the development of new technological logistics are environmental requirements for the integration of technologies into the transport system. These trends are slowing down the development of International Logistics, which, compared to other industries, is slower to integrate Industry 4.0 technologies. This study combines macroeconomic factors that determine the prospects for the development of transport and logistics systems at the micro level. Зміна розвитку транспортних та логістичних систем відбувається з активною зміною технологій та приходом ери Індустрії 4.0. Це вимагає модернізації підходів до розвитку транспортно-логістичних систем на макро- та мікрорівнях. Дане дослідження має на меті визначити перспективу напрями розвитку та еволюції, з’ясувати існуючі перешкоди при інтеграції технологічних рішень транспортно-логістичних систем на макро- та мікрорівні. Це дослідження засноване на кількісній та якісній методології оцінки рівня інтеграції технологій у транспортно-логістичні системи для вивчення перспектив їх розвитку на мікрорівні. Для кількісної оцінки перспектив розвитку використовувались макроекономічні показники транспорту та логістики в контексті різних регіонів світу. Для якісної оцінки розвитку транспортно-логістичної системи наведено тематичне дослідження був використаний метод. Об'єктом дослідження була обрана логістична компанія Sensco Logistics Inc., Austin TX. На макрорівні країни з більш інноваційним сектором логістики мають сильніші показники механізми координації діяльності приватного сектору. Спрощення адміністративних процедур контролю та регулювання з боку державного сектору з метою сприяння торгівлі між ними країн є перспективним напрямком розвитку транспортних та логістичних систем. Такі реформи ефективніші у розвитку “жорсткої” транспортної інфраструктури. Інтеграція технологічних рішень Індустрії 4.0 у міжнародний логістичний сектор визначається політичними та правовими бар'єрами, особливо в країнах, що розвиваються. У країнах з низьким рівнем доходів реформи жорсткої та м'якої інфраструктури перешкоджають розвитку логістичних компаній, які надають транспортні послуги. Це визначає національний рівень розвитку транспортно-логістичних систем і загалом глобальний рівень розвитку транспорту та логістики. У розвинених країнах правовими бар'єрами для розвитку нової технологічної логістики є екологічні вимоги до інтеграції технологій у транспортну систему. Ці тенденції уповільнюють розвиток міжнародної логістики, яка, порівняно з іншими галузями, повільніше інтегрує технології Industry 4.0. Це дослідження поєднує макроекономічні фактори, що визначають перспективи розвитку транспортно-логістичних систем на мікрорівні.
Оцінка перспективного розвитку транспортних та логістичних систем на макро- та мікрорівні в умовах промисловості 4.0 Інтеграція
Keywords: Transport and Logistics System; транспортно-логістична система; Logistics 4.0; логістика 4.0; Integration of Technologies into Logistics; інтеграція технологій у логістику; Technological Solutions of Logistics Companies; технологічні рішення логістичних компаній